Health and security risks of humanitarian aid workers during field missions: Experience of the International Red Cross. Issue 46 (March 2022) - Guisolan, S.C.; Ambrogi, M.; Meeussen, A.; Althaus, F.; Eperon, G.
Abstract: Background: Humanitarian disaster environments put relief workers at risk, both physically and mentally. Research looking at the growing humanitarian workforce's health and working conditions is lacking. Methods: A questionnaire was presented to ICRC (International Committee of the Red Cross) workers during debriefing between 2016 and 2018. Participants were queried about their experience abroad including security incidents (the primary objective), health, and malaria prevention. Descriptive statistics and multivariate logistic regressions were used for data analysis. Results: Security incidents were reported by 12% (95/796) of expatriates, mainly armed threats and attacks (83%, 79/95). Accidents or injuries occurred for 7.5% (60/796), of which 42% (25/60) were due to sporting activities and 22% (13/60) to road accidents. Many engaged in risky behaviours (15%, 119/795), such as driving too fast or inebriated (37%, 44/119) and/or engaging in unsafe sex, (unfamiliar partner, no condom) (71%; 84/119). Compliance to malaria prophylaxis was low 43% (113/263). Over 40% (324/795) found the mission more stressful than expected. Almost a third (28%, 219/796) reported worsened health on their return. Conclusions: Humanitarian aid workers display a worsening of their health when on mission due to violence, accidents and risky behaviours. To preserve their staff's wellbeing, humanitarian organizations should pay attention to medical history, pre-travel training specific to assignment, and continuous medical and psychological support.